Symbiotic microbes affect the expression of male reproductive genes in Glossina m. morsitans - Francesca Scolari; Geoffrey Michael Attardo; Emre Aksoy; Brian Weiss; Grazia Savini; Peter Takac; Adly Abd-Alla; Andrew Gordon Parker; Serap Aksoy; Anna Rodolfa Malacrida (BMC Microbiology, 2018)
Abstract Background Tsetse flies (Diptera, Glossinidae) display unique reproductive biology traits. Females reproduce through adenotrophic viviparity, nourishing the growing larva into their modified uterus until parturition. Males transfer their sperm and seminal fluid, produced by both testes and male accessory glands, in a spermatophore capsule transiently formed within the female reproductive tract upon mating. Both sexes are obligate blood feeders and have evolved tight relationships with endosymbionts, already shown to provide essential nutrients lacking in their diet. However, the partnership between tsetse and its symbionts has so far been investigated, at the molecular, genomic and metabolomics level, only in females, whereas the roles of microbiota in male reproduction are still unexplored. Results Here we begin unravelling the impact of microbiota on Glossina m. morsitans (G. morsitans) male reproductive biology by generating transcriptomes from the reproductive tissues of males deprived of their endosymbionts (aposymbiotic) via maternal antibiotic treatment and dietary supplementation. We then compared the transcriptional profiles of genes expressed in the male reproductive tract of normal and these aposymbiotic flies. We showed that microbiota removal impacts several male reproductive genes by depressing the activity of genes in the male accessory glands (MAGs), including sequences encoding seminal fluid proteins, and increasing expression of genes in the testes. In the MAGs, in particular, the expression of genes related to mating, immunity and seminal fluid components’ synthesis is reduced. In the testes, the absence of symbionts activates genes involved in the metabolic apparatus at the basis of male reproduction, including sperm production, motility and function. Conclusions Our findings mirrored the complementary roles male accessory glands and testes play in supporting male reproduction and open new avenues for disentangling the interplay between male insects and endosymbionts. From an applied perspective, unravelling the metabolic and functional relationships between tsetse symbionts and male reproductive physiology will provide fundamental information useful to understanding the biology underlying improved male reproductive success in tsetse. This information is of particular importance in the context of tsetse population control via Sterile Insect Technique (SIT) and its impact on trypanosomiasis transmission.